Reliability of a High-Intensity Endurance Cycling Test - O’Hara, J. P.; Thomas, A.; Seims, A.; Cooke, C. B.; King, R.F.G. J. (International Journal of Sports Medicine, 2012)
This study assessed the reproducibility of performance and selected metabolic variables during a variable high-intensity endurance cycling test. 8 trained male cyclists (age: 35.9±7.7 years, maximal oxygen uptake: 54.3±3.9 mL·kg − 1·min − 1) completed 4 high-intensity cycling tests, performed in consecutive weeks. The protocol comprised: 20 min of progressive incremental exercise, where the power output was increased by 5% maximal workload (Wmax) every 5 min from 70% Wmax to 85% Wmax; ten 90 s bouts at 90% Wmax, separated by 180 s at 55% Wmax; 90% Wmax until volitional exhaustion. Blood samples were drawn and heart rate was monitored throughout the protocol. There was no significant order effect between trials for time to exhaustion (mean: 4 113.0±60.8 s) or total distance covered (mean: 4 6126.2±1 968.7 m). Total time to exhaustion and total distance covered showed very high reliability with a mean coefficient of variation (CV) of 1.6% (95% Confidence Intervals (CI) 0.0±124.3 s) and CV of 2.2% (95% CI 0.0 ±1904.9 m), respectively. Variability in plasma glucose concentrations across the time points was very small (CV 0.46–4.3%, mean 95% CI 0.0±0.33 to 0.0±0.94 mmol·L − 1). Plasma lactate concentrations showed no test order effect. The reliability of performance and metabolic variables makes this protocol a valid test to evaluate nutritional interventions in endurance cycling.
Keywords: validity; performance; exercise testing; blood glucose; blood lactate; SRM Powermeters